20 Quality of Life of Hypertensive and Non-Hypertensive End Stage Renal Disease Patients Undergoing Hemodialysis. (November 2017) - Japar, Karunia Valeriani; Wibisono, Prio; Waren, Kalis; Vatvani, Akhil Deepak; Florence,; Lemuel, Theo Audi Yanto
Abstract : Background: With the increasing prevalence of hypertension, there has been a growing interest in understanding the health-related quality of life (HRQOL) of patients with hypertension. Although hypertension is often perceived as asymptomatic, it's relation with Quality of life (QoL) is still controversial. Objective: The aim of this study is to assess the QoL of End Stage Renal Disease (ESRD) who are on maintenance dialysis with or without hypertension. Methods: This is a multicenter cross sectional study that took place in 4 hemodialysis clinics in Jakarta from October to December 2016. QoLwas measured using WHOQOL-BREF containing 4 domains related to physical health, psychological, social relationships and environmental. Hypertension is defined as systolic BP ≥ 140mmHg or diastolic BP ≥ 90mmHg or previously taking antihypertensive medications. Analysis was carried out using T-test or Mann-Whitney, depending on the distribution of the data. Results: A total of 138 patients were collected, out of which 86(62.3%) were male. The mean age of the patients were 53.0(±12.5) years. The etiology of ESRD was mostly due to hypertension (56.5%) and diabetes (29.7%). The median duration of dialysis was 33(1–216) months. There were 106(76.8%) patients suffering from hypertension. The mean scores for physical health domain in the hypertensive and non-hypertensive patients were 54.8(±16.9) and 61.5(±15.4) respectively (p: 0.049). There was no significant difference between between the 2 groups for the other domains of QoL. Conclusion: Patients with hypertension have significantly lower physical health related QoL. Extra attention must be given to these group of patients in order to improve the QoL.